Measuring and Explaining Government Inefficiency in Developing Countries - Nicolas van de Sijpe; Glenn Rayp (Verein für Socialpolitik, Ausschuss für Entwicklungsländer, 2005)
We show the relevance of government expenditure inefficiency using the Barro (1990) model. We estimate government inefficiency for 52 developing countries using a data envelopment analysis. The estimated inefficiencies are subsequently used in a general to specific approach in order to identify their determinants. We find the government expenditure inefficiency is primarily determined by governance and political variables, and structural country variables. Economic policy determinants apparently count less. Government inefficiency of the Sub Saharan countries in the sample is substantially higher.
Keywords: O23; H50; H21; 330; Government inefficiency; data envelopment analysis; economic development